The Macroeconomics of Labor and Credit Market Imperfections - Wasmer, Etienne; Weil, Philippe (American Economic Review, 2004)
Credit market imperfections influence the labor market and aggregate economic activity. In turn, macroeconomic factors have an impact on the credit sector. To assess these effects in a tractable general-equilibrium framework, we introduce endogenous search frictions, in the spirit of Peter Diamond (1990), in both credit and labor markets. We demonstrate that credit frictions amplify macroeconomic volatility through a financial accelerator. The magnitude of this general-equilibrium accelerator is proportional to the credit gap, defined as the deviation of actual output from its perfect credit market level. We explore various extensions, notably endogenous wages.